Semiotics of Costume in Baamaaya Dance Suite of the Dagbamba - Kwakye-Opong, R. (Arakan Press, 2015)
The paper discusses the symbolisms and the aesthetics of costume in the Baamaaya Dance Suite among the Dagbamba in Northern Ghana. It looks at semiotics of costume from the general framework of non-verbal communication within the context of the dance. Costume within the framework of the dance will be interrogated based on gender sensitivity. Why the choice of feminist costume for the opposite sex?, The myth surrounding the choice of feminist costume for the opposite sex, as well as clothing representations, will be investigated on the cosmic world view of the Dagbamba. Through participant observation, interviews and content analysis, the paper posits that the feminist reflection of clothes on the men in the Baamaaya dance performance is rooted in the Dagbamba mythology. Again, the costumes are not only aesthetically applied, but they are also embedded with philosophies, symbolisms, signs, texture and elements that are impetus to the general framework of the dance.